Rationally designed hierarchical N-doped carbon@NiCo2O4 double-shelled nanoboxes for enhanced visible light CO2 reduction - Wang, Sibo (2020)
Here we demonstrate the delicate design and construction of hierarchical nitrogen-doped carbon@NiCo2O4 (NC@NiCo2O4) double-shelled nanoboxes for the photocatalytic reduction of CO2 with visible light. This smart design rationally combines the structural and functional advantages of catalytically active Co and Ni species with conductive nitrogen-doped carbon into a three-dimensional hollow nanoarchitecture, which can remarkably facilitate the migration and separation of photogenerated charge carriers, enhance the adsorption and concentration of CO2 molecules, and provide more active sites for photochemical reactions. Benefitting from these unique structural and compositional features, the hierarchical NC@NiCo2O4 double-shelled nanoboxes manifest considerable performance for the deoxygenative reduction of CO2 with a high CO-evolving rate (26.2 μmol h−1; 2.62 × 104 μmol h−1 g−1) and high stability.